Albumin Alters the Conformational Ensemble of Amyloid-β by Promiscuous Interactions: Implications for Amyloid Inhibition - Xie, Huisi; Guo, Cong (Frontiers in Molecular Biosciences, 2021)
Human serum albumin (HSA) is a key endogenous inhibitor of amyloid-b (Ab) aggregation. In vitro HSA inhibits Ab fibrillization and targets multiple species along the aggregation pathway including monomers, oligomers and protofibrils. Amyloid inhibition by HSA has both pathological implications and therapeutic potential, but the underlying molecular mechanism remains elusive. As a first step towards addressing this complex question, we studied the interactions of an Ab42 monomer with HSA by molecular dynamics simulations. To adequately sample the conformational space, we adapted the replica exchange with solute tempering (REST) method to selectively heat the Ab42 peptide in the absence and presence of HSA. Ab42 binds to multiple sites on HSA with a preference to domain III and adopts various conformations that all differ from the free state. The b-sheet abundances of H14-E22 and A30-M33 regions are significantly reduced by HSA, so are the b-sheet lengths. HSA shifts the conformational ensemble towards more disordered states and alters the b-sheet association patterns. In particular, the frequent association of Q15-V24 and N27-V36 regions into a b-hairpin which is critical for aggregation is impeded. HSA primarily interacts with the latter b-region and the N-terminal charged residues. They form promiscuous interactions characterized by salt-bridges or hydrogen bonds at the edge of the peptide-protein interface and hydrophobic cores at the center. Consequently, intra-peptide interactions crucial for b-sheet formation are interfered. Our work builds the bridge between modification of Ab conformational ensemble and amyloid inhibition by HSA. It also illustrates the potential of the REST method in studying interactions between intrinsically disordered peptides and globular proteins.